Strategi Pemasaran dalam Menarik Nasabah Simpanan Wadiah di BMT Eka Mandiri Cabang Muntilan - Qurrata A’yun, Azkiya; Fitriyani, Yeny; Nur Alfianto, Achmad; Purwanto, Purwanto (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
Marketing strategy is the right step to face increasingly fierce competition in promoting a product in the era of globalization. Several analyzes can be done to determine the marketing strategy used by a company. Marketing strategies are useful for formulating company goals, such as increasing the number of customers at BMT Eka Mandiri Muntilan Branch. This research adopts a descriptive method with a qualitative approach. The 4P theory (product, price, place, promotion) is also applied in this study by analyzing customer responses using the AIDCA concept (Attention, Interest, Desire, Conviction, Action). The focus of the research is to understand the marketing strategy of wadiah savings at BMT Eka Mandiri Muntilan Branch and analyze its impact on saving interest. The results showed that BMT Eka Mandiri uses a 4P strategy that successfully creates aspects of buying interest, encouraging potential customers to buy and use wadiah savings products. This research is expected to provide information and become a reading material for the readers regarding the marketing strategies and the analysis conducted.